The Relationship Between Smartphone Addiction and Forward Head Posture in Junior High School Students in North Denpasar - Nanda Putra Wiguna; Nila Wahyuni; Agung Wiwiek Indrayani; Ari Wibawa; Sayu Aryantari Putri Thanaya (Jurnal Epidemiologi Kesehatan Komunitas, 2019)
ABSTRACTBackground:Nowadays, the smartphone has become an important requirement. The number of smartphone users and the duration of smartphone use is increasing rapidly, and the side effects can be detrimental one of them is forward head posture. The prevalence of forward head posture is greater women (24.1%) than men (9.1%).Methods:This study was an analytical observational study with a cross-sectional design.This research was conducted in April 2019 in SMP Negeri 2 Denpasar and SMP Negeri 4 Denpasar andincluding 56 samples, who were recruited through simple random sampling.Variables studied are smartphone addition was measured using the Smartphone Addiction Scale questionnaire, and forward head posture was measured by measuring craniovertebral angles. Data analysis was done using the Chi-Square test. Result: Based on this study, smartphone addiction was related to forward head posture. The research shows that as many as 45 samples had Smartphone Addiction (80.35%) while those who had forward head posture were 29 samples (51.78%).Conclusion : Ignorance of how to sort and choose the effects of globalization, especially smartphone use, which can lead to posture disorders. The factor recognized factors for the occurrences of the forward head posture the lack of education about ergonomic positions when using a smartphone. Parents are advised to set the right smartphone usage for children as early as possible.